1976
DOI: 10.1007/bf01796119
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary divergence and length of repetitive sequences in sea urchin DNA

Abstract: The organization of repetitive and single copy DNA sequences in sea urchin DNA has been examined with the single strand specific nuclease S1 from Aspergillus. Conditions and levels of enzyme were established so that single strand DNA was effectively digested while reassociated divergent repetitive duplexes remained enzyme resistant. About 25% of sea urchin DNA reassociates with repetitive kinetics to form S1 resistant duplexes of two distinct size classes derived from long and short repetitive sequences in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
32
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…The presence of reDetitive DN4A sequences in eukaryotic organisms is now well established (1)(2)(3)(4). Characterisation of the repeat elements by buoyant density centrifugation, renaturation kinetics and restriction enzyme digestion has demonstrated the existence of distinct families with little or no sequence homology between them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of reDetitive DN4A sequences in eukaryotic organisms is now well established (1)(2)(3)(4). Characterisation of the repeat elements by buoyant density centrifugation, renaturation kinetics and restriction enzyme digestion has demonstrated the existence of distinct families with little or no sequence homology between them.…”
Section: Introductionmentioning
confidence: 99%
“…The humn Alu family of repeats, for example, are scattered throughout the genome (7) whereas another set of complex repeat sequences, the human Alpha Rl family, and other "buoyant density" satellites appear to be localised near to the centromeric C IRL Pres Umited, 1 Falconb.rg Court, London W1V 5FG, U.K. Volume 9 Number 15 1981 regions of certain chromosomes (10).…”
Section: Introductionmentioning
confidence: 99%
“…Reassociated repetitive eukaryotic DNA typically melts over a much broader range of temperature, and with a lower average thermal stability, than does the corresponding native DNA. It is generally accepted that such profiles reflect the presence of many imperfectly paired duplexes resulting from reactions between divergent members of repetitive sequence families (5). The reduction in average thermal stability (tm) relative to native DNA can provide an estimate of the average base pair mismatch in a given population of duplexes in vitro (5) and thus of the average sequence divergence characterizing the families of repetitive DNA in a given sample.…”
mentioning
confidence: 99%
“…It is generally accepted that such profiles reflect the presence of many imperfectly paired duplexes resulting from reactions between divergent members of repetitive sequence families (5). The reduction in average thermal stability (tm) relative to native DNA can provide an estimate of the average base pair mismatch in a given population of duplexes in vitro (5) and thus of the average sequence divergence characterizing the families of repetitive DNA in a given sample. Recently, it has been possible to show that reassociated repetitive sequences from plants could be fractionated according to tm (by elution from hydroxyapatite), and each fraction then could be reassociated to yield duplexes with tm values similar to those of the original fraction from which they were derived (6,7).…”
mentioning
confidence: 99%
“…The calculations we presented earlier suggest that as much as 70% of rat repeated DNA may be longer than 1 kb. Britten et al (10) showed that almost 47% of isolated repeated sequence duplexes of sea urchin DNA are longer than 1 kb (mild S1 nuclease digestion). The smaller the fraction of true short repeats in a genome, the more difficult will be the isolation of the short repeat fraction free of long repeat contamination.…”
mentioning
confidence: 99%